2009
DOI: 10.1007/s10661-009-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fecal contamination indicator sterols in an Australian water supply system

Abstract: This paper reports a reconnaissance survey of the concentrations of sterol compounds (as indicators of fecal contamination) in a large water supply system in southeast Australia comprising a network of rivers, channels, and drains. Levels of coprostanol and cholestanol were determined in surface water and bottom sediment using gas chromatography-mass spectrometry analysis across 17 strategic sampling sites and over 12 months. Clear differences in the levels of fecal contamination were observed among sites. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…A study of an Australian water supply system comprised of rivers, channels and drains monitored only two sterols (coprostanol and cholesterol) for a longer period of time (12 months) and used cluster analyses to detect similarities among the sampling sites (Hussain et al, 2010). In this study, clustering of sites by sterol profile suggested four clusters that differed by the source.…”
Section: Chemometric Approach For Source Tracking Of Human and Poultrmentioning
confidence: 88%
“…A study of an Australian water supply system comprised of rivers, channels and drains monitored only two sterols (coprostanol and cholesterol) for a longer period of time (12 months) and used cluster analyses to detect similarities among the sampling sites (Hussain et al, 2010). In this study, clustering of sites by sterol profile suggested four clusters that differed by the source.…”
Section: Chemometric Approach For Source Tracking Of Human and Poultrmentioning
confidence: 88%
“…Since coprostanol is produced in the digestive tracts of mammals by microbial reduction of cholesterol, livestock waste is likely to be a main contaminant source for samples with high coprostanol contents. The extraction method of coprostanol for the groundwater samples was implemented according to the below and referring to Hussain et al (2010), though with some modification. In total, 800 mL of the water samples were acidified with 1.0 N HCl to pH 2-3.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have suggested alternative bacteria or viral indicators such as coliphages (Toranzos 1991, Beaudeau et al 2002, Lovelace 2004, Pseudomonas (Cabelli et al 1976), enterovirus (Gersburg 2004, Fuhrman et al 2005, Bacteroidales , and Clostridium perfringens (Bisson & Cabelli 1980, Fujioka & Shizumura 1985, Fujioka 1997, Rose 2004 on the premise that they may have a better correlation to swimmer-related illness than current bacterial indicators under certain conditions (Table 9.1). Chemical tracers (faecal sterols, caffeine, and optical brighteners) have also been considered as alternative or secondary indicators of surface water quality (Isobe et al 2004, Ferreira 2005, Hussain et al 2010 (Table 9.1).…”
Section: Alternative or Secondary Indicatorsmentioning
confidence: 99%